Does Transformational Leadership Matter in The Relationship Between Emotional Intelligence and Internationalization of Higher Education? - Rayeni, Mojgan Sharifi; Ali, Mazlan Bin; Azadavar, Ramin; Hasan, Norehan Abu (International Journal of Psychosocial Rehabilitation, 2020)
Emotional intelligence plays an important role in the development of leadership and the performance of organizations. However, little is known about the effect of emotional intelligence on transformational leadership and the internationalization of higher education. To address this gap, the present study examined the relationship between emotional intelligence, internationalization of higher education, and transformational leadership. Data collected from 283 top management of five universities in Malaysia was analyzed using PLS-SEM. The results showed that emotional intelligence was significantly and positively related to transformational leadership, and, in turn, transformational leadership was positively and significantly related to the internationalization of higher education. Furthermore, the findings revealed that transformational leadership mediated the relationship between emotional intelligence and internationalization of higher education. The results, discussions, implications, and limitations of the study are discussed